Theoretical investigation and prototype design for non-parallel squeeze film movement platform driven by standing waves. (March 2018) - Wei, Bin; Shaham, Ran; Bucher, Izhak
Abstract: In order to realize contactless levitation and movement of precision components, a new kind of acoustic prototype driven by standing waves utilizing reverse hydrodynamic effects of non-parallel squeeze film was proposed in this paper. Its mechanism of movement and levitation was revealed by the viscous fluid mechanics and dynamic lubrication theory. It is amazing that the reverse hydrodynamic effects made the levitated plate move along the opposite direction of gravitational tangential component, which was proved in the experiments. The bearing and pushing capacity is predicted by numerical calculation of Reynolds equation and a CFX model. A dimensionless parameter 'voltage difference ratio' was proposed to evaluate the deflection angle of a non-parallel squeeze film, which can guide the prototype design. Highlights: Acoustic movement plat form with non-parallel squeeze film driven by standing waves. Moving along the opposite direction of gravitational tangential component. 'Voltage difference ratio' was proposed to evaluate the deflection angle of non-parallel squeeze film. Have more advantages of bearing capacity and broadband domain control than traveling waves.